High-speed photonics interconnects - Chrostowski, Lukas; Iniewski, Krzysztof (Devices, circuits, and systems., 2013)
The book is designed to achieve two goals. It assembles the latest research in the field of photonics interconnects technology and exposes the reader to the myriad applications that this technology has enabled. The book is mean for advanced graduate researchers, as well as for academicians and professional researchers. Composed of work from experts at leading academic institutions and semiconductor companies, such as Intel, PMC-Sierra, and Vittesse, this resource will have a widespread appeal, as it requires minimal math and contains numerous illustrations--